How Name, Image and Likeness “Fit” in Sport Partnerships - Lane Wakefield; Kirk Wakefield; Jonathan A. Jensen; Greg Bennett (Journal of Applied Sports Management, 2021)
Sponsorship opportunities in college athletics have shifted dramatically as athletes have rights to name, image and likeness (NIL). NIL assets, once illegal for college athletes, are prime avenues for brands to reach college sports fans, the largest and most avid sports fan base in the US (Dosh, 2021). Our purpose is to evaluate how these changes “fit” into the overall sponsorship landscape and what will come next. With the impact on brands, properties and consumers over time, we narrow our discussion around “fit,” the most prevalent factor in academic sponsorship research (Wakefield et al., 2020)
Keywords: College Sports; NCAA; NIL; Sponsorships; Student-Athletes